Design and characterization of floating microspheres for rheumatoid arthritis - Yadav, Ramnaresh; Bhowmick, Mithun; Rathi, Vaishali; Rathi, Jagdish (Journal of Drug Delivery and Therapeutics, 2019)
Gastroretentive systems can remain in the gastric region for several hours and significantly prolong the gastric residence of the drugs. Prolonged gastric retention improves bioavailability, reduces drug waste, improve solubility of drugs that are less soluble in a high pH environment. It has application also for local drug delivery to the stomach and proximal small intestine. The main objective of any drug therapy is to achieve  a desire concentration of the drug in blood or tissue  which is therapeutically effective and nontoxic  for extended period of time, and this goal can  be achieved by proper design of sustain release  dosage regimen. Microspheres have been widely accepted as a mean to achieve oral and parenteral controlled release. The microspheres require a polymeric substance as a coating material or carrier. A number of different substances biodegradable as well as non-biodegradable have been investigated for the preparation of microspheres. The aim of this study is to prepare floating microspheres containing Sulfasalazineto achieve a controlled drug release profile suitable for peroral administration.Keywords: Gastroretentive, Sulfasalazine, sustain release, Microspheres